"Keep withstanding": Territory in the body, home and market in Xinjiang, China. (January 2021) - Tynen, Sarah
Abstract: Geographic literature has explored how territorialization occurs by multiple actors in material and symbolic spaces, especially in the home and body. Building on the important research in feminist geography concerning the body as territory, important questions remain: How do Uyghurs in China respond to state territory in their everyday lives? How does fear, pleasure, and mistrust constitute the social relations of territory? How do people experience and navigate state dispossession of territory? I use long-term ethnographic fieldwork to study these questions. China is a strong, authoritarian state with a monopoly on power and seemingly unlimited surveillance and policing capabilities. Uyghurs explored survival strategies that constituted social relations of territory as a node in overlapping networks in Xinjiang. My main argument is that despite a strong government presence, embodied Indigenous practices enabled survivance for the Uyghur people. People escaped the stress of government surveillance and policing by turning to material and symbolic modes of constituting embodied territory.